Mars Braciaca (RIB 278) at Haddon Hall, Derbyshire - Andrew Breeze (Language, Culture, Politics)
Braciaca, on an altar to Mars at Haddon Hall (near Bakewell, in the north Midlands of England), has been related to Welsh brag 'malt' and explained as 'he of (divine) intoxication'. Yet this is hard to see, and a new explanation from Welsh bragad 'army, host; battle' seems preferable. It ts the God of War better than 'malt' does (a product more apt for Bacchus than Mars). If so, Braciaca 'of the hosts' will be one of many terms from Roman Britain that Welsh (and related languages) can explain. To show this, we first consider Celtic attitudes to Mars, and then go on to brag and its cognates.